Factors influencing audit opinion of the Indonesian municipal governments’ financial statements - Bambang Pamungkas (Taylor & Francis Group, 2018)
This study aims to obtain empirical evidence whether the criteria of forming an audit opinion have been significantly effecting audit opinion of municipal government financial statements in Indonesia. The considerations for expressing audit opinion are the deficiency in the internal control system (ICS), the non-compliance with regulations and laws, and the non-conformance with the Government Accounting Standards (GAS). The deficiency in internal control is analyzed by the number of findings on three categories, namely the number of weaknesses in the internal control structure, deficiency in the controlling system of revenue and expenditure budget realization, and the weakness in the accounting and reporting controlling system. The non-compliance with legislation is measured by the number of administrative findings and the ratio between the value of findings to the total value of expenditures of either the findings of regional losses, the potential regional losses, and the revenue shortfall. The non-conformances with the government accounting standard is represented by the number of accounts that were not presented in accordance with the GAS. The study is conducted on 182 municipal government financial statements for 2016 and 2015 financial years with the result of both the non-compliance with the regulations that result in regional losses and the non-conformance with the GAS have a negative effect on audit opinion, whereas the other criteria of forming audit opinion show no effect on audit opinions.